Pembuatan Ekstraksi Nitrogen ZPT Alami Untuk Kebutuhan Pupuk Pada Tanaman - Zalukhu, Enjel Kristiani; Waruwu, Patricia Zeni Febriani; Halawa, Jefon Citrawan; Zebua, Teguh Wa’asaro; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2024)
This study aims to develop nitrogen extraction from natural growth regulators to support efficient and environmentally friendly organic farming. Experimental methods were used with biological materials such as bamboo shoots, bean sprouts, leaves, brown sugar, EM4, and coconut water. The procedure involved fermentation for seven days to produce liquid ZPT. The results showed that nitrogen extraction from these natural materials effectively increased the growth potential of plants. The color, texture, and composition of the solution changed during the fermentation process, reflecting the activity of microorganisms supporting the development of the ZPT. The discussion highlighted the potential of utilizing natural ZPT as an alternative to synthetic fertilizers that are expensive and have a negative impact on the environment. This research concludes that nitrogen extraction from biological materials is an innovative solution for sustainable agriculture with cost efficiency and minimal environmental impact. Large-scale implementation could extend its benefits to farming communities, particularly in agrarian regions such as Nias Islands.